PENGARUH WADAH KULTUR DAN KONSENTRASI SUMBER KARBON PADA PERBANYAKAN KENTANG ATLANTIK SECARA IN VITRO - Karyanti, Karyanti; Kristianto, Yosua Glen; Khairiyah, Hayat; Novita, Linda; Sukarnih, Tati; Rudiyana, Yayan; Sofia, Dewi Yustika (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2018)
The Effect of Culture Container and Carbon Source Concentration on In Vitro Shoot Propagation of Atlantic PotatoABSTRACTPotato is a food commodity that has the potential to support food diversification in Indonesia. There is an increasing demand for Atlantic potatoes as the raw material for processed potato products. The demand, which has not been met by the increased production, has been the cause of the ongoing potato import activities in Indonesia. The limitation of producing quality Atlantic potato seeds economically is one of the obstacles to increasing the production of Atlantic potatoes in Indonesia. The aim of this research was to study the effect of various table sugar concentrations as the carbon source and the type of the culture containers used for Atlantic potato shoot multiplication in vitro. The propagation was carried out in bioreactors and culture bottles with MS liquid medium + coconut water at a concentration of 150 mL/L medium, and 3 concentration levels of table sugar, namely 0; 7.5; and 15 g/L medium. The use of bioreactor significantly increased the height of the Atlantic potato plantlets. The use of bioreactor combined with table sugar addition decreased hyperhydricity level. The highest number of shoots, leaves, and roots were found at the table sugar concentration of 15 g/L medium in both containers.Keywords: bioreactor, micropropagation, shoot culture, Solanum tuberosum, sucroseÃ‚Â ABSTRAKKentang merupakan komoditas pangan yang berpotensi mendukung program diversifikasi pangan di Indonesia. Peningkatan permintaan terhadap kentang Atlantik sebagai bahan baku kentang olahan yang tak diimbangi dengan peningkatan produksi kentang Atlantik menjadi penyebab masih berlangsungnya impor kentang Atlantik di Indonesia. Keterbatasan menghasilkan benih kentang Atlantik berkualitas yang ekonomis merupakan salah satu hambatan dalam meningkatkan produksi kentang Atlantik di Indonesia. Penelitian ini bertujuan mempelajari pengaruh variasi konsentrasi sukrosa teknis sebagai sumber karbon dan penggunaan jenis wadah terhadap perbanyakkan tunas kentang Atlantik secara in vitro. Perbanyakkan tunas kentang Atlantik menggunakan media MS cair + 150 mL/L air kelapa dalam wadah bioreaktor dan botol kultur dengan 3 taraf konsentrasi sukrosa, yaitu 0; 7,5; dan 15 g/L media. Penggunaan bioreaktor secara signifikan meningkatkan tinggi planlet kentang Atlantik yang dihasilkan. Penggunaan bioreaktor yang dikombinasikan dengan penambahan sukrosa teknis menurunkan tingkat hiperhidrisitas. Tunas, daun, dan akar terbanyak dihasilkan oleh perlakuan sukrosa teknis 15 g/L media dalam kedua jenis wadah.Kata Kunci: bioreaktor, kultur tunas, mikropropagasi, Solanum tuberosum, sukrosa